Prediction of site specific coverage and cell shape for outdoor microcells - Bertoni, H.L.; Piazzi, L.; Liang, G.; Nai Wo; Wong, E. (Electro '96 : professional program proceedings, April 30-May 2, 1996, Garden State Convention Center, Somerset, New Jersey, 1996)
The design of future wireless communication systems employing microcells will require a flexible tool for determining the coverage area based on site specific features. In this paper, the accuracy of a ray based algorithm for predicting the sector average path loss in residential and high rise environments is investigated by comparison with measurements. Measurements were taken in residential and in high rise environments. In the residential environment building heights ranged from 1 to 3 stories and the base station antenna was near rooftop levels, propagation between the base station and the mobile consisted mainly of paths which went over the intervening buildings. This was validated by good agreement with the measurements for the antenna above the rooftops, and fair agreement for the antenna below the rooftops. In the high rise environment the buildings were significantly higher than the base station antenna, so that the dominant contributions to the signal at the receiver are due to propagation around the buildings. Once again the predictions corresponded well the measurements.